Microbiological Evaluation of Protected Environments During Patient Occupancy - Bodey, Gerald P. (1971)
Microbiological monitoring has been conducted in two life island (LI) units and two laminar airflow (LAF) rooms while they were occupied by patients undergoing cancer chemotherapy. There were only 5 organisms per 1,000 ft(3) of air sampled in LAF rooms, 31 organisms in LI units, and over 3,000 organisms in regular hospital rooms. None of the floor samples obtained from hospital rooms was sterile, compared to over 70% in LAF rooms. The rate of deposition of organisms onto settling plates was one organism per 4.5 hr in LAF rooms compared to one organism per 0.08 hr in hospital rooms. Potential pathogens were isolated much more frequently from environmental samples obtained from hospital rooms than from LI units or LAF rooms. Two sites of persistent contamination arose in the LAF rooms: the vinyl tile flooring and the water supply system. Over half of the potential pathogens cultured from the protected environment units were cultured initially from the patients who occupied the units.